Curriculum Development Management in Media Officer Activities in Pondok Pesantren An-Nidhom Cirebon City - Yesi Aristin; Taqiyuddin Taqiyuddin; Mukhlisoh Mukhlisoh (JIEM (Journal of Islamic Education Management), 2023)
Managing an educational institution is necessary so that the implementation of education can be run well and is structured. The curriculum is used as a reference in the learning process for more directed practice. Cirebon City An-Nidhom Islamic Boarding School is a non-formal Islamic educational institution that uses the "Kitab Kuning" as their source of knowledge. One of the activities besides the reviewing is the media officer relating to the use of technology. The purpose of this research is to describe how the management of curriculum development in Cirebon City An-Nidzom Islamic Boarding School media officer activities. The method used in this research is qualitative with descriptive analysis. The data are obtained through interviews, observation, and documentation. Data analysis techniques used descriptive qualitative through data reduction, data presentation, and taking a conclusion The results of this study will indicate that the management of the curriculum in media officer activities at the Cirebon City An-Nidhom Islamic Boarding School hasn't been structured and organized due to a lack of human resources, resulting in neglect of various media officer programs. For this reason, it is hoped that in the future, the management will be able to manage it properly.